Um modelo de suporte à decisão para seleção e priorização de KPIs baseados nos sete desperdícios do Lean Logistics e no Balanced Scorecard - Santos, José Rodolfo Laurentino dos (2021)
The definition of an efficient set of performance indicators can guide the organizations to reach its main strategics objectives. It is understood as an efficiente set, when the organization have a number of indicators that cover its process but in an adequate amount. In addition, such indicators can be used as a guide for the deployment of all tactical and operational actions that organizations perform. Methodologies based on continuous improvement use indicators for the measurement and control of leaner alternatives in its processes, among which, the logistical processes. In parallel, strategic deployment methodologies such as the Balanced Scorecard (BSC) assist in translating the organizations strategic objectives into their operations. The Lean Logistics is a derivation of lean manufacturing, which focuses on the logistics processes between supply chain agents as well as the internal logistics processes of organization. The focus of lean logistics is to oppose the seven wastes of lean philosophy, applied to logistics processes, as: Overprodutction, Waiting, Transportation, Motion, Defects, Inventory and over-processing. Relating the themes presented, this research proposes a model for the selection and definition of a set of indicadors or KPIs (key performance indicators), necessary for the measurement and control of seven wastes of lean logistics, prioritized by the organization’s strategy, based on the BSC four perspectives. This set of indicators, identified through a literature review, was grouped according to the seven wastes, and used later within a selection method. The use of DEMATEL and AHP decision support tools, helped to choose the main indicators, primarily through the waste in which they were grouped and after ranked considering the BSC’s perspectives as criteria. The research is done through a case study, carried out in a large company, in a moment of the implementation of lean philosophy. As a result, a model proposal was developed to assist the definition and prioritization of indicators, in addition to providing a list of indicators ranked to control the logistics processes, based on the seven wastes of lean logistics and the perspectives of the BSC. These indicators were sufficient to cover the 7 wastes according to the initial grouping. The solution suggested by the methodology considers a final set of seven indicators ranked according to the preference of decision makers in operational and strategic biases within the applied case study, considering the indicators based on financial perspectives as more applicable to support the strategies of the organization.